Liver stiffness in Fontan patients: the effect of respiration and food intake - Braun, Annabell; Mühlberg, Richard; Fischer, Marcus; Haas, Nikolaus A.; Meyer, Zora (Frontiers in Medicine, 2023)
Objectives For several years, patients with single ventricle hearts have been palliated according to the Fontan principle. One well known long-term consequence in these patients is the Fontan-associated liver disease and fibrosis, which occurs due to the chronically increased Central Venous Pressure (CVP) after Fontan palliation. It carries an increased risk of liver cirrhosis and hepatocellular carcinoma over time. Liver elastography (LE) is a non-invasive, safe, and feasible ultrasound method to determine liver stiffness and the stage of liver fibrosis. Usually, this examination must be performed in a sober condition and strict inspiratory hold to optimize the results and may therefore be difficult to perform on children as a routine examination. However, the influence of food intake and respiration on these results in Fontan patients is unclear. To optimize the implementation for this examination especially in children, the effects of food intake and breathing maneuvers on liver stiffness in patients with Fontan circulation were investigated. Methods For this prospective study, 25 Fontan patients (group 1) and 50 healthy volunteers (group 2) were examined. The two groups were additionally divided into two age categories (group 1a: 10–19 years; group 1b: 20–29 years; group 2a: 15–19 years; group 2b: 20–25 years). Liver stiffness was measured by liver elastography once before food intake (=T0, with 6 h of fasting). Subsequently the participants consumed a standardized chocolate drink (500 mL) with nutritional distribution corresponding to a standardized meal (600 kcal). Liver stiffness was then determined 15, 30, 45, 60, 90, 120, 150, and 180 min after ingestion. Each measurement of liver stiffness was performed during maximal inspiratory and expiratory holds. The study was reviewed and approved by the responsible ethics committee. Results In group 2 there was a significant increase in liver stiffness after food intake at T15, T30, and T45 during inspiration measurements (T0 = 4.0 kPa vs. T15 = 4.9 kPa, difference = 22.5%; T0 = 4.0 kPa vs. T30 = 4.9 kPa difference = 22.5%; T0 = 4.0 kPa vs. T45 = 4.3 kPa difference = 7.5%), as well as during expiration at T15 and T30 (T0 = 4.5 kPa vs. T15 = 5.1 kPa, difference = 14.7%; T0 = 4.5 kPa vs. T30 = 4.9 kPa difference = 7.8%). Whereas in Fontan patients (group 1) liver stiffness did not differ significantly at any time between fasting (T0) and postprandial values. The respiratory maneuvers in the healthy subjects (group 2) differed significantly only before food intake (T0) (group 2: insp = 3.97 kPa vs. exp. = 4.48 kPa difference = 11.3%). In the Fontan group (group 1), there was no significant difference between the respiratory phases at any point. The different age categories showed no significant difference in liver stiffness. Conclusion With these results we could demonstrate for the first time that in Fontan patients the time of food intake (i.e., fasting) has no clinical significance for the values obtained in liver elastography. We could also demonstrate that the breathing maneuvers during the examination had only minimal clinical impact on the results of liver elastography in patients with normal circulation and no effect in patients with Fontan-circulation. Consequently, liver elastography for Fontan patients is reliable independently of food intake and breathing maneuvers and can also be performed on younger patients, who are unable to follow breathing commands or longer fasting periods, without any impairment of the results. These results should encourage a routine use of LE in the follow-up of Fontan patients.